Examining the Effect of Islamic Corporate Social Responsibility on Profitability: Return on Assets as a Mediator - Ika, Desi; Azhar, M. Karya Satya (Institut Bisnis dan Informatika Kesatuan, 2026)
Islamic Corporate Social Responsibility (ICSR) has become a critical strategy for companies to enhance sustainability and stakeholder trust, yet its impact on financial performance remains debated. This study examines the empirical impact of Islamic Corporate Social Responsibility (ICSR) on profitability, utilizing Islamic Corporate Governance (ICG) and Return on Assets (ROA) within a mediating framework. A descriptive-associative design with a quantitative approach was employed, covering all companies listed on the Jakarta Islamic Index (JII). A purposive sample of eight companies consistently listed between 2013 and 2023 was selected. Data analysis was conducted using path analysis through Structural Equation Modeling (SEM) with SmartPLS software. The findings reveal that while ICSR significantly influences ICG, it does not exert a direct impact on ROA. Furthermore, although ROA is a critical factor for ICG, its role as a mediator in the relationship between ICSR and ICG was not supported by the data. These results suggest that ICSR serves primarily to strengthen governance mechanisms rather than directly driving immediate financial profitability.